Avaliação do uso vacinal de peptídeos baseados na proteína OmpA de Shigella spp. - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Shigellosis is a diarrheal disease caused by gram-negative bacteria of the genus Shigella sp. occurs mainly in children under 5 years old that contribute to a high rate of infant morbidity and mortality, thus characterizing a serious global public health problem. Because of this, the World Health Organization (WHO) determined a priority for the development of new strategies to combat shigellosis. Among these strategies, the search for effective and low-cost vaccines is an eminent need Thus, this study proposed to immunize mice of the BALB/c lineage with a synthetic peptide (P2) selected from a sequence of the outer membrane protein A (OmpA) of Shigella, via intranasal routes using Bacillus subtilis spores as carrier structure; and intraperitoneally using the KLH carrier protein (keyhole limpet hemocyanin), and later to challenge them with a lethal dose of this pathogen (S. flexneri 5a M90T), to assess the protection capacity established by the two pathways. Anti-peptide antibodies produced during the immunizations and after the challenge were analyzed using the immunoenzymatic ELISA test. After the challenge, mice were evaluated for weight and death surveillance. The results showed that intranasal immunization was not efficient in the production of systemic antibodies, and consequently little protective against Shigella infection. In contrast, intraperitoneal immunization showed high levels of anti-peptide antibodies and showed considerable protective capacity against infection caused by this pathogen. Thus, the synthetic peptide P2, when administered intraperitoneally, showed immunogenic and protective potential against shigellosis, confirming that it is a good candidate for a vaccine.
Evaluation of the vaccine use of peptides based on the OmpA protein from Shigella spp.
Keywords: Shigella - Tratamento; Shigella - Vacinação; Intestinos - Doenças; CIENCIAS BIOLOGICAS; Vacina; Shigella; Peptídeo sintético; Intranasal; Intraperitoneal